The dignity of the different – Towards a Christian ethics for a pluralistic society - Huber, Wolfgang (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
From the perspective of three periods of professional experience of the author – twelve years as a church-related researcher, fourteen years as a full-time professor of ethics and sixteen years as a church leader – the essay expresses the need to address the role of christian ethics for society anew. It shows how and why, in the next period of his research and public involvement, the author wants to take the pluralistic character of modern societies even more seriously than in some of his previous approaches. In order to do so and to reach some ethical agreement in pluralistic societies, a central prerequisite is to make room for different voices to be heard. For only then we shall find a relevant, overlapping consensus amongst these voices. This, furthermore, requires rethinking of the forces – religious or otherwise - behind why human beings are motivated to act according to their ethical convictions. In all of this a useful guiding principle may be found in the so-called dignity of the different.